Tracing lineage by phenotypic and genotypic markers in Salmonella enterica subsp. enterica serovar 1,4,[5],12:i:- and Salmonella Typhimurium isolated in state of São Paulo, Brazil - Ana T Tavechio; Sueli A Fernandes; Ângela CR Ghilardi; Geoff Soule; Rafiq Ahmed; Carmo EA Melles (Memorias do Instituto Oswaldo Cruz, 2009)
Fifty-three Salmonella 1,4,[5],12:i:- and 45 Salmonella Typhimurium strains were characterised using phage typing, plasmid profiles and pulsed-field gel electrophoresis (PFGE) for comparison. The majority of the strains were subdivided into definitive type (DT) 41 (22.6%) and DT 193 (18%) and the 60-MDa plasmid was detected in 94.3% and 84.4% of strains, respectively. Genetic diversity was observed among all strains and 90% presented a > 70% similarity through PFGE analysis. These results suggest a close relationship between Salmonella 1,4,[5],12:i:- and Salmonella Typhimurium at the serotype level.